Comparison between two self-guided tinnitus pitch matching methods - Santacruz, Jose L.; de Kleine, Emile; van Dijk, Pim (Frontiers in Aging Neuroscience, 2023)
Tinnitus pitch matching is a procedure by which the frequency of an external sound is manipulated in such a way that its pitch matches the one of the tinnitus. The correct measure of the tinnitus pitch plays an important role in the effectiveness of many sound-based therapies. To date, this assessment is difficult due to the subjective nature of tinnitus. Some of the existing pitch matching methods present a challenge for both patients and clinicians, and require multiple adjustments of frequency and loudness, which becomes increasingly difficult in case of coexisting hearing loss. In this paper, we present the comparison in terms of reliability between two self-guided pitch matching methods: the method of adjustment (MOA) and the multiple-choice method (MCM). Twenty participants with chronic tinnitus and hearing loss underwent the 2 assessments in 2 different sessions, one week apart. Measures of intraclass correlation (ICC) and difference in octaves (OD) within-method and within-session were obtained. Both methods presented good reliability, and the obtained values of ICC and OD suggested that both methods might measure a different aspect of tinnitus.